PEMBERDAYAAN KELOMPOK WANITA TANI DI DESA SOMPAK MELALUI DIVERSIFIKASI OLAHAN BERBASIS LABU KUNING - Zulfita, Dwi; Rahayu, Sri (Universitas Esa Unggul, 2019)
The problem faced by the Padagi farmer group and the Nuk Diri farmer group is that yellow pumpkins are only sold in young condition for their needs as vegetables or sold their leaves so that farmers often face problems in living standards below the poverty line. The young pumpkin fruit is sold from house to house or sold at the village market. Partners do not know how to diversify various pumpkin processed products that have added value, are more resistant to storage and have a higher selling price. The method used in this activity is counseling, demonstration, training, and guidance in the process of making various pumpkins processed products such as nuggets, jams, brownies, sticks, and jelly candies. The evaluation was carried out on all activities. From this activity, it can be concluded that the level of partner participation has a positive impact on program implementation during training and mentoring.Ã‚Â Keywords: processed products, pumpkin, group of female farmers.